2022
DOI: 10.1093/jcde/qwab076
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance comparative analysis of nanofluid flows at an oblique stagnation point considering Xue model: a solar application

Abstract: This exploration aims to study the comparison of heat transfer capabilities of two nanofluid oblique, steady stagnation-point flow combinations comprising single-walled carbon/water (SWCNHs/water) and multiwalled carbon nanotube/water (MWCNTs/water) toward a stretching surface influenced by nonlinear thermal radiation employing the Xue model. This envisaged comparison model is inimitable and still scarce in the literature. Relying on the Tiwari–Das nanofluid model, a mathematical framework is constructed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Last but not the least, we try to solve equations (12) , (13) of the type (see Refs. [ 8 , 27 ]) When the flow is normal, it is represented by and when it is tangent, it is represented by . Because of this here and.…”
Section: Model Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Last but not the least, we try to solve equations (12) , (13) of the type (see Refs. [ 8 , 27 ]) When the flow is normal, it is represented by and when it is tangent, it is represented by . Because of this here and.…”
Section: Model Formulationmentioning
confidence: 99%
“…There are various industrial processes and applications that rely on stagnation point flow, like dip coating and metallic molding. In the area of the stagnation point flow, the pressure gradient and heat transfer are both seen to be at their highest levels [ 8 ]. Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because nanofluids have a pivoting role in electro-mechanical gadgets, heat exchange, advanced cooling systems, etc. A good number of experimental and theoretical studies have been conducted with various combinations of the nanoparticles and base fluids [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Among the distinct heat transport mode, convection with addition of CCHFM (Cattaneo Christov Heat Flux Model) is one of the prominent sources to upshot the heat transfer inside the working nanofluid. Recently, many studies [28][29][30][31] reported in this regard by taking various sorts of working nanofluids synthesized by different metals and host solvents. The literature revealed that inside temperature of the nanofluids could be enriched by inducing different physical phenomena in the modeling of the heat transfer problem.…”
Section: Introductionmentioning
confidence: 99%